2018
DOI: 10.1371/journal.pone.0198119
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of tobacco use in the United Arab Emirates Healthy Future (UAEHFS) pilot study

Abstract: IntroductionSelf-reported tobacco use in the United Arab Emirates is among the highest in the region. Use of tobacco products other than cigarettes is widespread, but little is known about specific behavior use patterns. There have been no studies that have biochemically verified smoking status.MethodsThe UAE Healthy Future Study (UAEHFS) seeks to understand the causes of non-communicable diseases through a 20,000-person cohort study. During the study pilot, 517 Emirati nationals were recruited to complete a q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
46
4

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 43 publications
(53 citation statements)
references
References 25 publications
3
46
4
Order By: Relevance
“…Expatriate workers account for almost 80% of the UAE population and about two-thirds of them are South Asian migrant workers from India, Pakistan and Bangladesh. [11] Research on the prevalence of tobacco use among UAE nationals (Emiratis) has been previously reported (24.3% in males and 0.8% in females), [12] however, there have been no studies on tobacco use among South Asian migrants in the UAE or any Gulf countries. In the current study we aimed to estimate the prevalence of, and factors associated with cigarette smoking and smokeless tobacco use among South Asian migrants in the United Arab Emirates who originated from India, Pakistan and Bangladesh.…”
Section: Introductionmentioning
confidence: 99%
“…Expatriate workers account for almost 80% of the UAE population and about two-thirds of them are South Asian migrant workers from India, Pakistan and Bangladesh. [11] Research on the prevalence of tobacco use among UAE nationals (Emiratis) has been previously reported (24.3% in males and 0.8% in females), [12] however, there have been no studies on tobacco use among South Asian migrants in the UAE or any Gulf countries. In the current study we aimed to estimate the prevalence of, and factors associated with cigarette smoking and smokeless tobacco use among South Asian migrants in the United Arab Emirates who originated from India, Pakistan and Bangladesh.…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, all this data is based on surveys and are, therefore, not consistent. In 2018, Al-Houqani et al [36] compared in a pilot study the self-reported tobacco use of 399 UAE nationals with the validation of the smoking status via cotinine testing in urine samples. They found that 42% of men and 9% of women were positive for cotinine versus the self-reported tobacco use of 36% men and 3% women.…”
Section: Discussionmentioning
confidence: 99%
“…The study provides a sound rationale for using the epidemiological survey that COPD is often only diagnosed until it is clinically apparent and moderately advanced, however patients may still be symptomatic, with an impact on quality of life 11 . Reviewing the prevalence figures, they appear to be very conservative, such as a 1.90% prevalence for the United Arab Emirates, where tobacco use is self-reported in 36% of the male population 46 .…”
Section: Discussionmentioning
confidence: 99%